Обзор сверчков подсемейства Nemobiinae (Orthoptera, Gryllidae) фауны СССР - Горохов, А.В. (Вестник зоологии, 1981)
Three species which were earlier related to the Pteronemobius J a c . genus are excluded from it. Two of them are transferred to the Dianemobius V i c k e r y genus, and the 3d one is identified as a new genus, Stenonemobius gen. n.